Standardized flow cytometry for highly sensitive MRD measurements in B-cell acute lymphoblastic leukemia - Theunissen, Prisca; Mejstrikova, Ester; Sedek, Lukasz; van der Sluijs-Gelling, Alita J; Gaipa, Giuseppe; Bartels, Marius; Sobral da Costa, Elaine; Kotrová, Michaela; Novakova, Michaela; Sonneveld, Edwin; Buracchi, Chiara; Bonaccorso, Paola; et al. (Blood, 2017)
A fully-standardized EuroFlow 8-color antibody panel and laboratory procedure was stepwise designed to measure minimal residual disease (MRD) in B-cell precursor (BCP) acute lymphoblastic leukemia (ALL) patients with a sensitivity of ≤10(-5), comparable to real-time quantitative polymerase chain reaction (RQ-PCR)-based MRD detection via antigen-receptor rearrangements. Leukocyte markers and the corresponding antibodies and fluorochromes were selected based on their contribution in separating BCP-ALL cells from normal/regenerating BCP cells in multidimensional principal component analyses. After 5 multicenter design-test-evaluate-redesign phases with a total of 319 BCP-ALL patients at diagnosis, two 8-color antibody tubes were selected, which allowed separation between normal and malignant BCP cells in 99% of studied patients. These 2 tubes were tested with a new erythrocyte bulk-lysis protocol allowing acquisition of high cell numbers in 377 bone marrow follow-up samples of 178 BCP-ALL patients. Comparison with RQ-PCR-based MRD data showed a clear positive relation between the percentage concordant cases and the number of cells acquired. For those samples with >4 million cells acquired, concordant results were obtained in 93% of samples. Most discordances were clarified upon high-throughput sequencing of antigen-receptor rearrangements and blind multicenter reanalysis of flow cytometric data, resulting in an unprecedented concordance of 98% (97% for samples with MRD < 0.01%). In conclusion, the fully standardized EuroFlow BCP-ALL MRD strategy is applicable in >98% of patients with sensitivities at least similar to RQ-PCR (≤10(-5)), if sufficient cells (>4 × 10(6), preferably more) are evaluated.
Keywords: dospělí; Neoplasm, Residual; Female; Infant; dítě; předškolní dítě; novorozenec; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; průtoková cytometrie; Adult; mladý dospělý; genová přestavba; ženské pohlaví; Adolescent; lidé; Infant, Newborn; Sensitivity and Specificity; Flow Cytometry; reziduální nádor; senzitivita a specificita; Receptors, Antigen, B-Cell; Male; kojenec; Aged; mladiství; Child, Preschool; Young Adult; Gene Rearrangement; receptory antigenů B-buněk; lidé středního věku; Child; senioři; mužské pohlaví; pre-B-buněčná leukemie; Middle Aged; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction; Humans